Determination of carbon emissions from hybrid road vehicles by mathematical modelling - Gheorghe Neamțu; Ioan ȚINCU; Marinela INȚĂ (Journal of Research and Innovation for Sustainable Society)
This scientific paper presents an own research and an original point of view on the technical, mathematical and economical acceptance of road vehicle emissions. Specialists argue that practical experimentation through active type determinations can bring remarkable results in any field. In order to demonstrate practically and mathematically the current claims of the specialists, the present paper presents the actual results of some experiments obtained and some considerations on the mathematical model used for the validation of the objective functions, i.e. the CO2 emissions obtained experimentally with specific measuring accuracy, on vehicles with hybrid propulsion. The proposed research also represents the authors' point of view, which is supported by the proposals made by the World Health Organization to reduce the speed of traffic in urban areas from 50 km/h to 30 km/h, with the aim of reducing the number of traffic accidents, as well as pollution with chemical and noise noxious substances and vibrations. The results of the tests carried out on urban roads were supplemented by the results of the tests carried out on motorways outside urban areas for comparative purposes, applying defensive driving methods (eco-driving). Thus, the paper presents the mathematical model and its validation applied on carbon dioxide (CO2) emissions obtained under real driving conditions of road vehicles. Finally, some conclusions and research directions of the modelling are presented.